Effect of Health Literacy Promotion on Alcohol Drinking Behavior by Gamification Activities in Ethnic Adolescents - chomsri, pimpisa; Matrakul, Mullika; Henkeaw, Wichaya; Surat, Soontaree (Health Science Journal of Thailand, 2025)
This research aims to investigate the effectiveness of gamification on health knowledge regarding alcohol consumption behavior among ethnic adolescents. This research was a multiphase design study. It is divided into two phases: 1st Phase is a cross-sectional study with the samples of 230 individuals, selected using stratified random sampling and proportionally calculated and 2nd phase involves dividing the samples into an experimental group of 27 individuals and a control group of 27 individuals, selected using block-stratified random sampling. Data collection tools include a questionnaire divided into three parts: personal information, health knowledge assessment, and alcohol consumption problem assessment. The research intervention tool is a gamification activity focusing on health knowledge regarding alcohol consumption behavior. Data analysis employs statistical methods such as paired t-tests and odds ratios. The research findings revealed that the majority of samples have health knowledge levels ranging from fair to poor, from 60.87% to 30.87%, respectively. Furthermore, the majority of samples engaged in low-risk drinking behavior (93.48%), with a small percentage engaging in risky or dangerous drinking (6.52%). After a 6-week period of gamified learning activities, the experimental group showed significantly lower rates of low-risk drinking compared to the control group, at 2.42 times higher (OR: 2.42). In conclusion, promoting alcohol knowledge through gamified learning effectively reduces moderate to high-risk drinking behaviors.